Altered spectral localization cues disrupt the development of the auditory space map in the superior colliculus of the ferret. - Schnupp, J; King, A; Carlile, S (1998)
Spectral localization cues provided by the outer ear are utilized in the construction of the auditory space map in the superior colliculus (SC). The role of the outer ear in the development of this map was examined by recording from the SC of anesthetized, adult ferrets in which the pinna and concha had been removed in infancy. The acoustical consequences of this procedure were assessed by recording outer ear impulse responses via a probe-tube microphone implanted in the wall of the ear canal. Both monaural and binaural spectral cues normally show a number of asymmetric features within the horizontal plane, which allow azimuthal locations on either side of the interaural axis to be discriminated. These features were eliminated or altered by chronic pinnectomy. The responses of auditory units in the SC to noise bursts presented in the free field were examined at sound levels of approximately 10 and 25 dB above unit threshold. After bilateral pinnectomy, the representation of auditory space was severely degraded at both sound levels. In contrast to normal ferrets, many units had bilobed azimuthal response profiles, indicating that they were unable to resolve sound locations on either side of the interaural axis. There was also much less order in the distribution of best azimuths or elevations of those units that were tuned to a single direction. Some units were tuned to locations that extended much further into the hemifield ipsilateral to the recording side than the normal range of best azimuths. Unilateral removal of the outer ear, which disrupts the monaural spectral cues for one side only, had a much smaller effect on the development of the auditory representation. At supra- and near-threshold sound levels, the representation of sound azimuth in the SC on both sides of the brain was less scattered than that found after bilateral pinna removal. Nevertheless, units with bilobed responses, broader tuning, and inappropriate best azimuths were observed in both the left and right SC of ferrets in which the left pinna and concha had been removed in infancy. These data illustrate that the localization cues provided by the outer ear play a critical role in the development of the auditory space map in the SC. In contrast to other manipulations of either auditory or visual inputs, the map does not appear to adapt to the changes in spectral cues brought about by pinna removal, suggesting that residual binaural cues are, by themselves, insufficient for its normal maturation.